Model Hybrid Learning untuk Peningkatan Skill Pemasaran Syariah melalui Media Sosial dan Aplikasi Mobile: Studi Empiris pada Pelaku Ekonomi Kreatif - Zuhrinal Nawawi; Ruli Pebrina Br Sitepu (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study examines the implementation of a hybrid learning model to enhance sharia marketing skills through social media and mobile applications among creative economy actors. By combining online and face-to-face learning, the model aims to provide flexibility and a comprehensive learning experience aligned with sharia principles such as honesty and business ethics. This literature review analyzes supporting factors, challenges, and the effectiveness of hybrid learning in the context of sharia-based digital marketing. Findings indicate that hybrid learning significantly improves digital competencies and sharia marketing skills, provided there is adequate technological infrastructure, adaptive curriculum, and sufficient mentoring. Social media and mobile applications are proven effective tools for market expansion, yet challenges in technology access and digital literacy must be addressed to fully optimize digital marketing potential in accordance with Islamic values. The study offers strategic recommendations for developing relevant and practical sharia marketing training in the digital era.